Gastric Metastasis of Primary Neuroendocrine Tumor of Skin: Rare Tumor with Rare Presentation - Osama, Md Ali; Rao, Seema; Mittal, Tarun; Kumar, Sandeep (Journal of Laboratory Physicians, 2023)
Merkel cell carcinoma (MCC) is a rare primary neuroendocrine tumor of the skin. It has an aggressive biological behavior and shows early local and distant metastasis. Diagnosis of MCC is a challenge and requires confirmation by immunohistochemistry (IHC). However, metastasis of MCC to the stomach is extremely uncommon and is rarely reported in the literature. We hereby describe a patient with gastric metastasis of MCC, who presented with black tarry stool and was finally diagnosed on the basis of clinical history, histology, and IHC.
Keywords: cutaneous; Merkel cell carcinoma; metastasis; neuroendocrine; stomach